2023
DOI: 10.1155/2023/8166825
|View full text |Cite
|
Sign up to set email alerts
|

Work Readiness, Decision‐Making Self‐Efficacy, and Career Exploration among Engineering Students: A Two‐Step Framework

Abstract: Prior to entering the workforce, engineering students are expected to be highly skilled and contribute to decision-making with confidence in their abilities. Despite this, most students are lacking in these areas. Engineering students typically have a hard time finding work because they lack the necessary skills and are unable to take decisions with confidence. Accordingly, the Washington accord created job-ready features for engineering students that contain core knowledge and design (FKD), project management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Lastly, personality associates fundamental choices in life, including life partner, profession, and career. As it corroborates the study of Makki, Feng, Waqar, & Adhikari (2023), putting into contextualization that suitability is the priority of teachers' desire, especially in making career jobs and work trades. Career implies social identity.…”
Section:  Significant Influence Of Teacher Self-efficacy On Career S...supporting
confidence: 72%
See 1 more Smart Citation
“…Lastly, personality associates fundamental choices in life, including life partner, profession, and career. As it corroborates the study of Makki, Feng, Waqar, & Adhikari (2023), putting into contextualization that suitability is the priority of teachers' desire, especially in making career jobs and work trades. Career implies social identity.…”
Section:  Significant Influence Of Teacher Self-efficacy On Career S...supporting
confidence: 72%
“…The field of, and just recently, this set of variables was tested in engineering. The study showed that self-efficacy has a significant impact and relation to career self-management (Makki et al, 2023). The Malaysian University surveyed engineers who showed skillfulness in their field in contribution to their career growth decision-making.…”
Section:  Career Self-managementmentioning
confidence: 99%